If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4/3x-2(9-1/3x)=-7/3x+9
We move all terms to the left:
4/3x-2(9-1/3x)-(-7/3x+9)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 3x)!=0
x!=0/1
x!=0
x∈R
Domain of the equation: 3x+9)!=0We add all the numbers together, and all the variables
x∈R
4/3x-2(-1/3x+9)-(-7/3x+9)=0
We multiply parentheses
4/3x+2x-(-7/3x+9)-18=0
We get rid of parentheses
4/3x+2x+7/3x-9-18=0
We multiply all the terms by the denominator
2x*3x-9*3x-18*3x+4+7=0
We add all the numbers together, and all the variables
2x*3x-9*3x-18*3x+11=0
Wy multiply elements
6x^2-27x-54x+11=0
We add all the numbers together, and all the variables
6x^2-81x+11=0
a = 6; b = -81; c = +11;
Δ = b2-4ac
Δ = -812-4·6·11
Δ = 6297
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-81)-\sqrt{6297}}{2*6}=\frac{81-\sqrt{6297}}{12} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-81)+\sqrt{6297}}{2*6}=\frac{81+\sqrt{6297}}{12} $
| 7r-6r-1=6 | | -4(x+4)+7x=-40 | | 12+(x+5)=144 | | 3t-3t+t-1=13 | | 12(x+4=5) | | 3y+5y-7y-1=5 | | 4x=-3x=14 | | 17+14m=-19 | | 000000000000000000=m | | (s-50)+(s-49)=s-10 | | 50000000000000000000000000000x5000000000000000000000000000=10 | | 22x=17x-175 | | 6a-2a-4a+3a=15 | | x-2=2x+5 | | 4n+4n-4n-2n-n=1 | | 75+-10x=-15 | | 11x=6x+4 | | -g+2(3+g)=5(g+1) | | -99160=1700-55g | | 20h-17h+h+2h=12 | | 1/2r+2(3/4r-1)=1/4r+6= | | -g+2(3+g=5(g+1) | | x/x/8+19=30 | | 10c-c=18 | | -12j+10j-3j=-5 | | 0.75n=35 | | 20t-9t=-11 | | 5x+14=-45-10x | | 6t−5t=16 | | 2x-13=3×+8 | | 20n-28=10n+12 | | x/x0.6=8.9 |